INTEGRASI PEMBELAJARAN DEEP LEARNING, dan PENGEMBANGAN MATERI PAI DALAM PEMBELAJARAN ABAD 21 - Orizza Sativa Azahra; Rohadatul Aisi; Zulvia Rahmi; Darul Ilmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid advancement of technology and the demands of 21st-century competencies require innovation in education systems, including Islamic Religious Education (PAI). This article discusses the integration of deep learning approaches in the development of PAI materials to foster students who are not only intellectually capable but also spiritually, morally, and socially profound. This study aims to analyze the concept of deep learning within the context of PAI learning, identify integrative strategies relevant to 21st-century learning characteristics, and explore its implications for curriculum and instructional model development. The research employs a qualitative descriptive approach using a literature review method, examining various sources, journals, and previous studies related to deep learning and Islamic education. The findings indicate that integrating deep learning into PAI can be implemented through project-based learning, spiritual reflection, collaboration, and contextual problem-solving that emphasize critical thinking, creativity, communication, and collaboration skills. Furthermore, the development of PAI materials should be aligned with contemporary issues such as digital literacy, religious moderation, and the cultivation of Islamic character relevant to global life. In conclusion, the application of deep learning in Islamic Religious Education enhances students’ holistic potential and provides an effective response to the challenges of 21st-century education, which demands a balance between knowledge, skills, and spiritual values.